A look at Venus - Spangenburg, Ray, 1939-; Moser, Diane, 1944- (New York : F. Watts, 2001)
Provides a description of Venus, and looks at how scientists have studied the planet.
Includes bibliographical references (p. 102) and index.
7.0
5-8
Keywords: Venus (Planet)